2018
DOI: 10.2147/ndt.s155144
|View full text |Cite
|
Sign up to set email alerts
|

High serum levels of 8-OHdG are an independent predictor of post-stroke depression in Chinese stroke survivors

Abstract: PurposeAlthough previous studies have investigated oxidative stress biomarkers in association with depression in non-stroke subjects, the association between oxidative deoxyribonucleic acid damage and post-stroke depression (PSD) remains unelucidated.Patients and methodsTwo hundred forty-one first-ever ischemic stroke patients were consecutively recruited within the first 24 h of stroke onset and were followed up at 1 month. Serum 8-hydroxy-2′-deoxyguanosine (8-OHdG) and catalase (CAT) levels were measured wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…27 Several studies have reported that free radicals are also involved in depression pathophysiology. 17,28,29 This study observed higher MDA levels in the depressed post-stroke group compared to the group without depression (p = 0.024). This is due to the vulnerability of brain tissue to oxidative stressors, given its high oxygen consumption and the high PUFA content of brain tissue.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…27 Several studies have reported that free radicals are also involved in depression pathophysiology. 17,28,29 This study observed higher MDA levels in the depressed post-stroke group compared to the group without depression (p = 0.024). This is due to the vulnerability of brain tissue to oxidative stressors, given its high oxygen consumption and the high PUFA content of brain tissue.…”
Section: Discussionmentioning
confidence: 55%
“…12,30,31 Liu's study also found that elevated 8-OhdG in the acute phase was correlated with one-month poststroke depression. 29 These arguments imply that peripheral 8-OhdG levels can serve as an indicator of the oxidative process in the brain. 30 In this study, it was found that MDA serum level was significantly higher in the post-stroke depression group than in the non-depression group (p=0.024).…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Liu et al [26], 241 ischemic stroke patients were consecutively recruited within the first 24h of stroke symptom onset and were followed up at 1 month. Serum 8-OHdG and catalase (CAT) levels were measured within 24h of hospital admission.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, T2DM patients usually suffer from a variety of mental health problems 4. Depression, a common mental disorder, is also a common complication of stroke 5. Nowadays, poststroke depression (PSD) has become a serious problem for T2DM patients.…”
Section: Introductionmentioning
confidence: 99%